Investigation of Immunomodulation Effects of Ethanolic Neem Seeds (Azadirachta indica) Extract on Induced Immune Response in BALB/C Mice with Vibrio alginolyticus Whole An - Ihsan Dhari Awad (Journal of Global Pharma Technology, 2016)
The Current study was studied the immunomoduatory potentials of Ethanolic Neem seed extract in treated mice with Vibrio alginolyticus whole antigen through estimation the phagocytic activity of and lymphocyte proliferations as well as estimation of the serum fractions to evaluate the humoral immune response . The study was divided into 4 groups: Group (I) was included treated mice with normal saline. Group II was included mice treated with Vibrio alginolyticus antigen only , Group,(III): included mice were treated with (200 ug /Kg) of the neem extract combination with Vibrio alginolyticus antigen ,finally , Group IV included mice were treated with (300 ug /Kg) of the neem extract combination with Vibrio alginolyticus antigen. The results of NBT index and MTT test were revealed group III and group IV showed highly significant increase (P≤ 0.05) comparison with other Groups .More further results of gel electrophoresis in current study were showed the level of Gamma globulin serum, Alpha-1 level, Alpha-2 level, Alpha-beta level were highly significantly in Group III and Group IV comparison with other groups. In other hands in this study the results were showed there is no significant difference between group III and group IV in NBT index and MTT test as well as Gel electrophoreses. Depending on the results of current study the Ethanolic Neem extract had a positive immunomodutory effect on the induced immune response.Keywords: Neem Seeds extract, Immunomodulatory Effects, Vibrio alginolyticus whole antigen, Immune response.